Cause-Specific Deaths in Non–Dialysis-Dependent CKD - Navaneethan, Sankar D. (J Am Soc Nephrol, 2015)
CKD is associated with higher risk of death, but details regarding differences in cause-specific death in CKD are unclear. We examined the leading causes of death among a non–dialysis-dependent CKD population using an electronic medical record-based CKD registry in a large healthcare system and the Ohio Department of Health mortality files. We included 33,478 white and 5042 black patients with CKD who resided in Ohio between January 2005 and September 2009 and had two measurements of eGFR<60 ml/min per 1.73 m(2) obtained 90 days apart. Causes of death (before ESRD) were classified into cardiovascular, malignancy, and non-cardiovascular/non-malignancy diseases and non–disease-related causes. During a median follow-up of 2.3 years, 6661 of 38,520 patients (17%) with CKD died. Cardiovascular diseases (34.7%) and malignant neoplasms (31.8%) were the leading causes of death, with malignancy-related deaths more common among those with earlier stages of kidney disease. After adjusting for covariates, each 5 ml/min per 1.73 m(2) decline in eGFR was associated with higher risk of death due to cardiovascular disease (hazard ratio [HR], 1.10; 95% confidence interval [95% CI], 1.08 to 1.12) and non-cardiovascular/non-malignancy diseases (HR, 1.12; 95% CI, 1.09 to 1.14) but not to malignancy. In the adjusted models, blacks had overall-mortality hazard ratios similar to those of whites but higher hazard ratios for cardiovascular deaths. Further studies to confirm these findings and explain the mechanisms for differences are warranted. In addition to lowering cardiovascular burden in CKD, efforts to target known risk factors for cancer at the population level are needed.